2010
DOI: 10.1111/j.1349-7006.2010.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation mechanisms of Sonic Hedgehog in breast cancer

Abstract: Sonic Hedgehog (Shh) plays an essential role in vertebrate organogenesis as well as the development of some cancers, including breast cancer. The aim of the present study was to characterize more precisely its role in breast carcinogenesis and elucidate its regulation mechanisms. The expression of Shh was investigated in 97 breast carcinomas and 22 paired non-tumorous tissues (distant from the primary tumor) by immunohistochemistry and in four breast cell lines by Western blotting. We also analyzed the methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 22 publications
8
76
0
Order By: Relevance
“…In this series, elevated expression level of SMO correlated with the presence of nodal disease, implicating its role in metastasis and disease progression [42]. Autocrine activation of the Hh pathway has also been shown in breast cancer, both in cell lines and tumoral tissue studies [43][44][45]. In a study by Kubo et al, overexpression of SHH and GLI1 was detected in virtually all of the 52 breast cancer specimens examined [43].…”
Section: Autocrine Stimulationmentioning
confidence: 51%
See 1 more Smart Citation
“…In this series, elevated expression level of SMO correlated with the presence of nodal disease, implicating its role in metastasis and disease progression [42]. Autocrine activation of the Hh pathway has also been shown in breast cancer, both in cell lines and tumoral tissue studies [43][44][45]. In a study by Kubo et al, overexpression of SHH and GLI1 was detected in virtually all of the 52 breast cancer specimens examined [43].…”
Section: Autocrine Stimulationmentioning
confidence: 51%
“…In a study by Kubo et al, overexpression of SHH and GLI1 was detected in virtually all of the 52 breast cancer specimens examined [43]. In another series, the overexpression of SHH in breast cancers was shown to be secondary to hypomethylation of the ligand promoter as well as NF-B upregulation [45]. Furthermore, akin to studies in lung cancers, inhibition of Hh pathway using cyclopamine led to suppression of proliferation in breast cancer cell lines in a dose-dependent manner [43].…”
Section: Autocrine Stimulationmentioning
confidence: 95%
“…Transcriptional activation occurs through the glioma-associated oncogene homolog (GLI) proteins family, resulting in activation of target genes (19). Aberrant activation of the Hh pathway has been linked to multiple types of human cancer, characterized by high expression levels of Shh, ptch, Smo, and GLI-1 (20)(21)(22)(23). They are also detectable in several leukemic cell lines with drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…SMO is expressed at higher amounts in Ductal carcinoma in situ and invasive ductal carcinoma (IDC), where its constitutive activation in mouse mammary glands brings about ductal dysplasia (Moraes et al 2009). Immunohistological identification of SHH was higher in breast cancers comparing with normal tissue (Cui et al 2010). Moreover, the Hh signaling pathway was discovered to be activated in the CSC-enriched CD44…”
Section: Hedgehog (Hh) Pathwaymentioning
confidence: 90%
“…Brain cancers have inactivating PTCH1 mutations (Hahn et al 1996), GLI1 was highly expressed in 26 % of primary GBMs and 57 % of cell lines (Bar et al 2007) and GLI1 shRNA brought about a critical diminishing in glioma development in vitro (Bao et al 2006) Breast cancers showed loss of PTCH1 and expansion in the GLI1 region (Naylor et al 2005), immunohistological identification of SHH was higher in breast cancers (Cui et al 2010), Moreover, the Hh signaling pathway is activated in breast CSC (Tanaka et al 2009) Hh signaling components are actually activated in advanced human colon cancer cells and their CSCs (Varnat et al 2010), GLI1 expression was increased in colon CSCs (Varnat et al 2010). Hence, metastatic colon cancers could conceivably be treated by blocking Hh signaling (Varnat et al 2010) ensnared a vital role for Notch signaling in the selfrenewal and maintenance of CSCs (Purow et al 2005).…”
Section: Notch Pathwaymentioning
confidence: 99%